PALEOZOIC PLATFORM DEPOSITS AND PRECAMBRIAN SUBSALT COMPLEXES OF THE LEFT-BANK ZONE OF THE YENISEY RIVER. NEW CANDIDATES FOR OIL AND GAS PROSPECTING - Dashkevich N.N.; Kashtanov P.A. (My University, 1990)
Data obtained in regional geophysical studies by the Yeniseygeofizika Corporation on the southeastern margin of the West Siberian Block have led to a new interpretation of the geological structure and developmental history of this region, and a new view on its oil and gas potential. The principal geological conclusions, based on an analysis of all geological and geophysical data are given in this paper.
Keywords: Paleozoic; Precambrian; Paleozoic; Precambrian; Палеозой; Докембрий